Implementation of the Pentahelix Approach in Developing Tourism During the Covid-19 Pandemic (Study on Sumberbiru Tourism Village, Jombang Regency) - Ahmad Bachtiar Arif; Zainul Arifin; Edriana Pangestuti (Sekolah Pascasarjana Universitas Brawijaya, 2022)
This research was conducted with the aim of seeing how much of the contribution made by stakeholders in the pentahelix approach, which includes academia, business, community, government, and media in developing tourist destinations in Sumberbiru Tourism Village, Jombang Regency during the covid-19 pandemic. The problems found in this study, namely: poor tourism management, poor tourism institutions, and inadequate accessibility. This research uses a qualitative approach with a case study method. Researchers also use SWOT analysis to plan tourism development strategies based on the situation in the field. The results of the study indicate that the government acts as an initiator by inviting various pentahelix stakeholders to work together in the Sumberbiru Tourism Village development program. All parties contribute to tourism development according to their respective fields by conducting various programs, such as training, mentoring, providing capital assistance, and building tourism supporting facilities. The existence of a tourism development program with pentahelix is to help overcome existing problems, not solve the whole problem.